2014
DOI: 10.1289/ehp.1306816
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Concentrations of 2,4-Dichlorophenol and 2,5-Dichlorophenol in the U.S. Population (National Health and Nutrition Examination Survey, 2003–2010): Trends and Predictors

Abstract: Background: 2,4-Dichlorophenol (2,4-DCP), 2,5-dichlorophenol (2,5-DCP), and their precursors are widely used in industry and in consumer products. Urinary concentrations of these dichlorophenols (DCPs) have been measured as part of four National Health and Nutrition Examination Survey (NHANES) cycles in order to assess the exposure to these compounds or their precursors among the general U.S. population.Objectives: We identified predictors and evaluated trends in DCP concentrations according to race/ethnicity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 16 publications
5
32
0
Order By: Relevance
“…Social and behavioral factors might significantly contribute to p-DCB exposure, which is supported by the study conducted by Chin et al 27 in which p-DCB concentrations in indoors was found differed among households and the cities studied. In accordance with our findings, Ye et al 29 found that household income and race/ethnicity were significant predictors of urinary concentrations of DCP above the 95th percentile. Furthermore, our study shows that the geometric mean of urinary concentrations of 2,5-DCP in US adult participants (20-79 years of age, n = 3063) was much higher than that in the German population (18-69 years of age, n = 692), based on the 1998 German Environmental Survey.…”
Section: Discussionsupporting
confidence: 93%
“…Social and behavioral factors might significantly contribute to p-DCB exposure, which is supported by the study conducted by Chin et al 27 in which p-DCB concentrations in indoors was found differed among households and the cities studied. In accordance with our findings, Ye et al 29 found that household income and race/ethnicity were significant predictors of urinary concentrations of DCP above the 95th percentile. Furthermore, our study shows that the geometric mean of urinary concentrations of 2,5-DCP in US adult participants (20-79 years of age, n = 3063) was much higher than that in the German population (18-69 years of age, n = 692), based on the 1998 German Environmental Survey.…”
Section: Discussionsupporting
confidence: 93%
“…This assumption is also supported by a recent study on dichlorophenols in the US population. 37 In addition, dichlorophenols seem to be different from triclosan with respect to its effect on IgE levels. While triclosan was reported not to be significantly associated with total serum IgE levels, 30 we found that dichlorophenols were positively associated with total serum IgE levels in the entire study sample.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding potential health effects of 2,5-DCP and 2,4-DCP is critical, given the high prevalence (81%) of Americans with evidence of exposure to these chemicals 8. The specific mechanisms by which 2,5-DCP and 2,4-DCP may influence health are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about associations of these environmental exposures with other health conditions, such as lung diseases, cardiovascular diseases (CVDs) and cancer in adult humans. Considering the pervasiveness of exposure to these chemicals,8 and laboratory animal studies suggesting that they have metabolic effects,21 22 there is a need to comprehensively evaluate whether these chemicals are associated with common medical conditions.…”
Section: Introductionmentioning
confidence: 99%